Oxydativ enzymek hisztokémiai kimutatásának jelentősége kísérletes agy-laesiók környéki és távoli hatásának megítélésében [The significance of histochemical demonstration of oxidative enzymes in the interpretation of local and remote effects of experimental brain lesions] - Bara Dénes (MORPHOLÓGIAI ÉS IGAZSÁGÜGYI ORVOSI SZEMLE, 1975)
In cortex, habenular- or hypothalamic regions of white rats electrocoagulation was carried out. Animals were killed from 6 days to 5 months after the operation. Serial slides of the brain were investigated by the aid of a reaction of SDH, alfa-GPDH, LDH, G6PDH, TPND. Group of neurons around the lesion may show a decreased, normal and increased activity of the enzymes investigated. As for the far effect of the lesion in case of the injury of the postcomissural fornix changes could have to be revealed in the corpus mamillare. Activization of neuroglia is marked by the increase of the reaction of G6PDH, LDH and TPNDH. Enzyme activity of cells of microglial origin at the beginning seems to be significant, later on, when the activity of phagocytes comes to the end it decreases to the minimum. Regeneration of cells of the leptomeninges and their role in demarcation of the process is marked by the increase of enzyme activity.